Association between five novel anthropometric indices and erectile dysfunction in US adults from NHANES database - Ningning Xu; Haoxi Zou; Huanying Xu; Yanfen Chen; Qidan Wen; Xiaoyan Xing; Suzhen Wu (Scientific Reports)
Abstract Erectile Dysfunction (ED) is the leading cause of sexual dysfunction affecting hundreds of millions of men worldwide, and has been described as an important public health problem. The association of five novel anthropometrics related to obesity, lipids and glucose with ED remains unclear. To investigate the association of lipid accumulation products index (LAP), triglyceride glucose index (TyG), waist triglyceride index (WTI), weight-adjusted-waist index (WWI) and a body shape index (ABSI) with ED. Cross-sectional data from the NHANES were used. Participants were adults aged 20–85 y from 2001 to 2004. The analysis of logistic regressions, smooth curve fitting, subgroup analyses and generalized addition model were performed to examine the relationship between five novel anthropometric indicators and the prevalence of ED. An overall 1413 adult men were included in the study. After adjusting for confounding factors, the results of multiple regression analysis showed, ED positively correlated with LAP(OR = 1.0031, P < 0.05), TyG(OR = 1.2981, P < 0.05), WTI(OR = 1.4220, P < 0.05), WWI(OR = 1.6043, P < 0.001), and ABSI(OR = 1.6211, P < 0.05). Smoothed curve fitting and subgroup analyses proved the stability of the relationship. This cross-sectional study showed a positive correlation between these five novel anthropometric indicators (LAP, TyG, WTI, WWI, ABSI) and ED. Further studies are needed to explore their association better and the underlying mechanisms.